Decision support system for selecting the best pesticide to eradicate pests on bean plants applying the Multi Attribute Utility Theory (MAUT) Approach - Ili Sama, Meliana; Kelen, Yoseph Pius Kurniawan; Gelu, Leonard Peter; S. Manek, Siprianus (Jurnal Simantec, 2025)
The selection of the right pesticide is very important in pest control efforts on bean plants to maximize yields and maintain crop quality. Often, farmers face a mismatch between expectations and reality related to the products they use. The market offers a wide range of pesticide products, each claiming to have certain advantages. Mismatches in pesticide selection can affect the yields obtained by farmers. This study aims to provide insight to farmers in choosing the best pesticide to control pests on bean plants. this study relies based on the Multi Attribute Utility Theory (MAUT) method as a means to weigh various options based on various aspects in a structured manner. to assess each criterion from various alternatives and provide a ranking of the best pesticide recommendations. The criteria considered include price, how it works, shelf life, number of pests, and its impact on bean plants. The application developed uses the PHP and MySQL programming languages. Based on the results of the study, the alternative pesticide Spinosad obtained the highest score of 0.85, making it the best recommendation.Keywords: Pesticide selection, Decision Support System (DSS), MAUT